Republic of Lithuania : Fiscal Transparency Evaluation. (IMF Staff Country Reports; Country Report ;, 2019)
This Fiscal Transparency Evaluation (FTE) paper on the Republic of Lithuania estimated Lithuania's public sector financial position to take a more comprehensive view of public finances in Lithuania. While Lithuania's overall assessment is comparable to or better than other EU Member States that have undergone an FTE, there is room for further improvement. While the Lithuanian authorities publish a large volume of fiscal reports, they are somewhat fragmented and not easily comparable. The paper also highlights that fiscal risk analysis and management also meets good or advanced practice in many areas but are slightly weaker than the other pillars of the evaluation. It is recommended to consolidate the present array of fiscal reports into a smaller number of user-friendly reports that improve the consistency and comparability of information, as well as its transparency. The report also provides a more detailed evaluation of Lithuania's fiscal transparency practices and recommended reform priorities.